Effect of vitamin B6 on GABA accumulation and growth stimulation in germinated mung beans - Sem, Tevin; Chamnipa, Nuttaporn; Vann, Kimroeun; Apiraksakorn, Jirawan (Asia-Pacific Journal of Science and Technology, 2024)
γ-aminobutyric acid (GABA) is an inhibitory neurotransmitter in animals and humans. It has several health advantages involving relief of anxiety and depression, as well as memory and immunity enhancement. GABA is also found in seeds as a reserve protein for plant growth. It is synthesized from glutamic acid by the glutamic acid decarboxylase (GAD) enzyme using vitamin B6 as a co-enzyme. To enhance the GABA content in bean sprouts, the effect of vitamin B6, in the form of pyridoxine hydrochloride (PN), on GABA accumulation in mung beans was examined. Supplementation of PN at various concentrations (1, 10, and 50 mg/L) was carried out in soaked and germinating mung beans. The results demonstrated a negative effect of PN on GABA accumulation. GABA was dramatically reduced with increased PN concentrations during soaking and germination. The highest GABA content was found in the control sample with no PN addition. Interestingly, PN showed an unexpected effect on promoting the growth of mung bean sprouts. The stem lengths of mung bean sprouts were significantly extended by increased PN concentrations. At 50 mg/L, PN induced a 35.6% elongation of stem length over that of a control. GABA content was negatively affected by PN in soaked seeds and germinated bean sprouts. However, it promotes mung bean growth during germination. PN is an effective growth stimulant for mung beans during germination.